Haven 5th Season disc 1 - Rose, Emily, 1981-; Bryant, Lucas; Balfour, Eric, 1977-; King, Stephen, 1947-; E1 Entertainment (Firm) (Port Washington, NY : Entertainment One Film, 2015)
Includes a storyline of a pair of paranormal investigators who star in their own reality show while on a fact finding mission to expose Haven's secrets.
See no evil -- Speak no evil -- Spotlight -- Much ado about Mara.
Title from container.
Based on "The Colorado kid" by Stephen King.
16x9 widescreen (1.78:1).
Emily Rose, Lucas Bryant, Eric Balfour.
Rating: TVMA.
DVD; 5.1 Dolby Digital.
Keywords: King, Stephen, -- 1947- -- Television adaptations; United States. -- Federal Bureau of Investigation -- Drama; Parapsychology -- Maine -- Drama; Television series; Horror television programs; Fantasy television programs; Television adaptations; Video recordings for the hearing impaired